PENYELESAIAN WANPRESTASI DENGAN JAMINAN TANAH PADA KOPERASI UNIT DESA (KUD) HASRAT JAYA KECAMATAN TAPUNG KABUPATEN KAMPAR - Ilham Kusuma Dhani; Firdaus '; Maryati Bachtiar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Village Unit Cooperatives (KUD) desire Jaya in the village Pagaruyung Tapung District of Kampar regency as container dealer credit to the community. One of the areas of cooperative efforts is felt increasingly increasingly needed by society is the savings and loan business. Savings and loans in the cooperative as an alternative means in terms of borrowing money or credit. In conducting the borrowing or credit both parties involved prior to an agreement being poured into an agreement. Giving credit as outlined in the borrowing agreement under Article 1754 to Article 1769 Civil Code. Thus the making of a credit agreement should refer or be subject to the provisions contained in the Civil Code and is based on an agreement between the parties so that there is no compulsion in terms of making this agreement. In a cash loan agreement does not cover possible defaults. Based on data obtained from the Village Unit Cooperatives (KUD) Desire Jaya period in 2015 there were 36 debtors who do a loan agreement at the Village Unit Cooperatives (KUD) desire Jaya. From that period there were six troubled borrowers, such as in the case of installment payment arrears or bad debts carried by the debtor.The purpose of this thesis, namely: first, to know the completion of defaults among members of a cooperative with the village unit cooperatives desire jaya acting outside the court, second, to see the efforts of the parties in the settlement of defaulting between members of the cooperative with the village unit cooperatives desire jaya ,This type of research is classified in socio-juridical research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted in the Village Unit Cooperatives desire Jaya in the village Pagaruyung Tapung District of Kampar, the data used is primary data, secondary data and data tertiary and research data collection techniques such as interviews, questionnaires and literature study.From the results, it can be concluded that the first settlement efforts undertaken by the Village Unit Cooperatives Jaya desire is through settlement amicably by giving a warning and a call to the party in default in the loan agreement on savings and loans belonging to the Village Unit Cooperatives desire Jaya. Second, efforts are made to menyelesaian defaulting cooperative members by providing extension of repayment periods on members who default. The author suggested that lending by village unit cooperatives jaya desire to members continues to be maintained because it helps members. The cooperative should be more cautious in lending to members and the cooperative must also make special rules for the lending and borrowing in terms of granting loans to its members.